Electrical neurostimulation in glaucoma with progressive vision loss - Erb, Carl; Eckert, Sophie; Gindorf, Pia; Köhler, Martin; Köhler, Thomas; Neuhann, Lukas; Neuhann, Thomas; Salzmann, Nadja; Schmickler, Stefanie; Ellrich, Jens (Bioelectronic Medicine, 2022)
Background: The retrospective study provides real-world evidence for long-term clinical efficacy of electrical optic nerve stimulation (ONS) in glaucoma with progressive vision loss. Methods: Seventy glaucoma patients (45 to 86 y) with progressive vision loss despite therapeutic reduction of intraocular pressure (IOP) underwent electrical ONS. Closed eyes were separately stimulated by bipolar rectangular pulses with stimulus intensities up to 1.2 mA sufficient to provoke phosphenes. Ten daily stimulation sessions within 2 weeks lasted about 80 min each. Right before ONS at baseline (PRE), vision loss was documented by static threshold perimetry and compared to the same assessment approximately 1 year afterwards (POST). Mean defect (MD) was defined as primary outcome parameter. Perimetries with a reliability factor (RF) of max. 20% were considered. Results: Perimetry follow-up of 101 eyes in 70 patients fulfilled the criterion of a max. 20% RF. Follow-up was performed on average 362.2 days after ONS. MD significantly decreased from PRE 14.0 dB (median) to POST 13.4 dB (p < 0.01). 64 eyes in 49 patients showed constant or reduced MD as compared to baseline (PRE 13.4 dB vs. POST 11.2 dB). In 37 eyes of 30 patients, MD increased from PRE 14.9 dB to POST 15.6 dB. Conclusions: Innovative treatments that preserve visual function through mechanisms other than lowering IOP are required for glaucoma with progressive vision loss. The present long-term data document progression halt in more than 63% of affected eyes after ONS and, thus, extend existing evidence from clinical trials.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Neuromodulation; Neuroprotection; Optic nerve; Perimetry; Restoration